A 1-Minute Re-warm Up at High-Intensity Improves Sprint Performance During the Loughborough Intermittent Shuttle Test - Yanaoka, Takuma; Iwata, Risa; Yoshimura, Akane; Hirose, Norikazu (Frontiers in Physiology, 2021)
Although a 3- to 7-minute re-warm up (RW) elicits performance and physiological benefits after half-time (HT), a time-efficient and feasible RW protocol is required for the use of a RW in the athletic setting. Thus, this study aimed to investigate the effect of a 1-minute RW at high-intensity on the performance and physiological responses during the Loughborough Intermittent Shuttle Test (LIST). In a randomized and counterbalanced cross-over design, 12 male amateur intermittent team sports players (soccer, basketball, handball, and lacrosse; age, 22±2 years; height, 1.70±0.08 m; body mass, 65.1±8.3 kg; body mass index, 22.4±1.9 kg·m-2; VO2max, 53.5±4.5 mL·kg-1·min-1) performed the LIST. The LIST comprised two 45-minute halves separated by a 15-minute HT. Each half comprised repetitions of exercise cycles consisting of 3×20-m walking, 1×20-m maximal sprint, 3×20-m jogging, and 3×20-m running. During the HT, the participants were assigned to a control trial (CON; 15-minute seated rest) or a RW trial (1-minute running at 90% of the maximal oxygen uptake after a 14-minute seated rest). Compared to the CON, the RW prevents reductions in sprint performance at the fourth and sixth periods of the LIST (fourth: 2.4%, p=0.002, d=1.68, sixth: 3.6%, p=0.012, d=1.74) and a decrement of gastrointestinal temperature during HT (0.5°C, p=0.010, d=1.41). Moreover, the RW decreased the electromyogram amplitude of maximal voluntary contraction after HT (12%, p=0.017, d=1.12) without a decrease of maximal voluntary contraction force, suggesting an increased neuromuscular efficiency (9%, p=0.048, d=0.58). The RW also increased the mean heart rate in the initial part of the second half (4 bpm, p=0.016, d=0.38). In conclusion, the RW improved sprint performance, core temperature, muscle activation, and heart rate in the second half of the LIST. The findings suggest that the RW should be recommended for intermittent team sports players when longer RWs are impossible.